Впровадження високоефективного обладнання для диспергування емульсій в технологічну лінію переробки молока - Самойчук, Кирило Олегович; Кюрчев, Сергій Володимирович; Паляничка, Надія Олександрівна; Верхоланцева, Валентина Олександрівна; Samoichuk, Kyryl; Kiurchev, Serhii; Palianychka, Nadiia; Verkholantseva, Valentyna (Мелітополь : ТДАТУ, 2022)
UA: Диспергування жирової емульсії шляхом гомогенізації є одним із найважливіших технологічних процесів в лінії переробки молока та виробництва молочної продукції. Від якості гомогенізації напряму залежать харчова цінність молока та продуктів його переробки, смакові властивості та засвоюваність його організмом людини. Тож до гомогенізаторів, які використовуються на підприємствах висуваються підвищені вимоги щодо якості кінцевого продукту. Окрім якості важливу роль в підборі обладнання відіграє показник питомих затрат енергії на процес. Так склалося, що найбільш розповсюджений тип гомогенізаторів є дуже енергозатратним. Дана стаття присвячена дослідженню ефективності диспергування жирової емульсії в імпульсному гомогенізаторі та впровадженню промислового зразка в технологічну лінію переробки молока. EN: The article is devoted to the study of effective equipment for dispersing emulsions and the introduction of industrial design in the technological line of milk processing. Dispersion of fat emulsion by homogenization is one of the most important technological processes in the line of milk processing and dairy production. The nutritional value of milk and products of its processing, taste properties and digestibility by the human body directly depend on the quality of homogenization. Therefore, the homogenizers used in enterprises are subject to increased requirements for the quality of the final product. In addition to quality, the indicator of specific energy costs for the process plays an important role in the selection of equipment. It so happened that the most common type of homogenizers is very energy consuming. As a result of the analysis, the most promising type of homogenizer was identified - pulsed, which allows to obtain a high degree of dispersion of the emulsion, with low energy consumption for the process. Dispersion of fat balls of milk in the pulse type of the homogenizer occurs due to the formation of a gradient of the emulsion flow rate, which occurs due to the pulse oscillation of the piston-drum. This leads to the grinding of the fat emulsion of milk and does not require large expenditures of energy. As a result of the study it was determined that the degree of homogenization in the pulse homogenizer is 4…5, and energy consumption for the process is 0.82 J / kg, which in turn indicates the high efficiency of technological equipment. In order to test the performance of the proposed design of pulse homogenizer in industrial conditions, a prototype of pulse homogenizer was developed, which subsequently passed production tests on the basis of the private enterprise «MZK «Pivdenniy "in the production line of pasteurized drinking milk. Tests have shown that the use of a pulse homogenizer has reduced the power per drive from 18.5 kW to 2 kW.
Introduction of highly efficient equipment for dispersion of emulsions into the technological line of milk processing
Впровадження високоефективного обладнання для диспергування емульсій в технологічну лінію переробки молока / К. О. Самойчук, С. В. Кюрчев, Н. О. Паляничка, В. О. Верхоланцева // Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Мелітополь : ТДАТУ, 2022. Вип. 12. том 2. C. 6-13.
Keywords: диспергування емульсій; гомогенізація; імпульсний гомогенізатор; якість; енергозатрати; технологічна лінія; жирова емульсія; ступінь гомогенізації; dispersion of emulsions; homogenization; pulse homogenizer; quality; energy consumption; production line, fat emulsion; degree of homogenization